Climate volatility and complexity: challenges for the Northwestern region of São Paulo State, Brazil - Avila, Douglas Carmo de (2024)
Climate change generates profound and interconnected impacts on natural ecosystems, hydropower generation, and agricultural productivity, directly affecting both society and the environment. The objective of this study was to characterize the changes in climate patterns in the northwestern region of São Paulo state, a strategic area both environmentally and economically due to its significant agricultural and livestock production. This study analyzed climate patterns and variability, connections with large-scale climatic oscillations, and long-term trends. Additionally, a dynamic assessment of drought events was conducted using the Standardized Precipitation Evapotranspiration Index (SPEI) across three accumulation scales, based on data from the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) and ERA5-Land atmospheric reanalysis. The results revealed significant shifts in precipitation and air temperature patterns, with weak correlation to large-scale climate oscillations, as well as indications of increasing drought severity in the region. These findings highlight the climatic volatility and complexity of the area and suggest the need for regional adaptations to address future climate challenges.